Evaluation of the risk of heart failure with tumour necrosis factor inhibitors A large-scale meta-analysis in immune-mediated inflammatory diseases - Galajda Noémi Ágnes (JOURNAL OF THE EUROPEAN ACADEMY OF DERMATOLOGY AND VENEREOLOGY, 2025)
Current therapeutic guidelines for immune-mediated inflammatory diseases (IMIDs) contraindicate the administration of tumour necrosis factor inhibitors (TNFis) in advanced heart failure (HF) and highlight the potential risk for new-onset HF. The current evidence has low certainty, and the results of studies in the past two decades have even challenged the recommendations regarding the impact of TNFis on the risk of HF.The objective was to systematically synthesize data on the risk of HF in TNFi-treated groups compared to non-treated controls in IMIDs.A systematic search was conducted in August 2023. Randomized controlled trials (RCTs) and non-randomized observational studies of IMID patients comparing groups receiving TNFis to non-TNFi-exposed controls were included. The outcome was the incidence of worsening, de novo, and composite HF. Random-effects meta-analysis was conducted using risk ratios (RR) with 95% confidence intervals (CIs) to pool data.The systematic search identified 49 studies, with 45 included in the quantitative analysis. For the worsening of HF, the pooled results of non-randomized studies showed no statistically significant risk-increasing effect of TNFis (RR = 1.18, 95% CI: 0.69-2.00). Analyses from both RCTs and non-randomized data indicated no increased risk of de novo HF in the TNFi-group compared to controls (RR = 0.87, 95% CI: 0.60-1.25 and RR = 0.86, 95% CI: 0.64-1.14, respectively). Similarly, no increased risk was found for composite (worsening and de novo) HF in the TNFi-treated group versus controls, pooling non-randomized data.Our findings indicate that TNFi-treated IMID patients do not have an increased risk for developing de novo HF, and no statistically significant risk enhancement could be observed in the risk of worsening HF with TNFis. Updating IMID guidelines should be considered regarding TNFis' non-risk increasing effect on de novo HF, whereas further validating data on the risk of worsening HF in TNFi-treated IMID patients is needed.